2021
DOI: 10.1039/d1ra02033a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thermal properties of phase change materials encapsulated in capped carbon nanotubes using molecular dynamics simulations

Abstract: Nanocluster enhanced PCM and metal doped CNT PCM systems have lower melting points than the normal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This is because the increased thermal energy causes the atoms vibrate more, which leads to a wider distribution of interatomic distances. As a result, the peak heights decrease and broaden as we move from T = 100K to 1000K [31]. Secondly, the deformation of the CNTs that may due to an applied strain can also be observed in the RDF plots.…”
Section: Effects Of Strain and Structural Analysismentioning
confidence: 93%
“…This is because the increased thermal energy causes the atoms vibrate more, which leads to a wider distribution of interatomic distances. As a result, the peak heights decrease and broaden as we move from T = 100K to 1000K [31]. Secondly, the deformation of the CNTs that may due to an applied strain can also be observed in the RDF plots.…”
Section: Effects Of Strain and Structural Analysismentioning
confidence: 93%
“…Abbaspour et al 109 investigated the encapsulation of n -eicosane and n -octadecane paraffin in different CNTs. The effect of adding various metal nanoclusters (such as Cu, Ag, and Al) to encapsulated n -octadecane was studied.…”
Section: Background Overviewmentioning
confidence: 99%
“…These materials have simple structures and can be simulated using the hybrid potentials of PCFF and Leonard-Jones using the molecular dynamics method as one of the best force fields. Albeit, as listed in Table 1, several force fields were utilized for PCMs such as Snyder force field, 28 Ryckaert and Bellemans, 29,31 COMPASS, 41,45,51,65–67,70,78–81,87,96,102–108 PYS, 43,50 Weber, 47 Buckingham, 49,54 NERD, 53,68,71–73,86,94,97 EIM, 55 GROMOS, 57,60,61 CHARMM, 59,83,90 OPLSAA, 64,109 Universal force field (UFF), 75,82,95,111 PCFF, 37,76,84,85 TraPPE, 77 Dreiding, 89 Born–Mayer–Huggins (BMH), 93 GAFF, 98,101 CVFF. 110 Some of the utilized force fields were placed in the simulated material box of Table 8 in {} signs.…”
Section: A Molecular Dynamics Based Grouping (Pcm Simulation Table)mentioning
confidence: 99%
“…[16] An increasing number of experimental studies have demonstrated that metal or metal oxide nanoparticles confined in capped car-bon nanotubes exhibit different catalytic activities, which provided confinement energy to enable prediction of confinement effects on catalytic activities in different reactions. [27] All of these indicate that materials in confined space show powerful application prospects.…”
Section: Introductionmentioning
confidence: 99%